2020
DOI: 10.1515/chem-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and potential ecological risk assessment of some trace elements in sediments and grey mangrove (Avicennia marina) along the Arabian Gulf coast, Saudi Arabia

Abstract: AbstractTo assess trace element concentrations (Zn, Cu, Pb, Cr, Cd and Ni) in the mangrove swamps along the Saudi coast of the Arabian Gulf, thirteen samples of surface sediment and leaves of grey mangrove, Avicennia marina were collected and analyzed. The detected trace element contents (μg g-1) in surface sediments were in the following descending order according to their mean values; Cr (49.18) > Zn (48.48) > Cu (43.06) &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 64 publications
3
0
0
Order By: Relevance
“…The Igeo values of Cd reflect unpolluted to moderately polluted northward and southward and from moderately to strongly polluted in the middle zone, recording an unpolluted degree at 21.74% of samples, unpolluted to moderately polluted at 17.39% of samples, moderately polluted at 39.13% of samples, and moderately to strongly polluted at 21.74% of samples. These findings are consistent with the results obtained by Alsamadany et al (2020). They reported that the higher contamination of cadmium might be attributed to non-point sources, such as wastewater drainage and agricultural runoff.…”
Section: Single Indicessupporting
confidence: 93%
“…The Igeo values of Cd reflect unpolluted to moderately polluted northward and southward and from moderately to strongly polluted in the middle zone, recording an unpolluted degree at 21.74% of samples, unpolluted to moderately polluted at 17.39% of samples, moderately polluted at 39.13% of samples, and moderately to strongly polluted at 21.74% of samples. These findings are consistent with the results obtained by Alsamadany et al (2020). They reported that the higher contamination of cadmium might be attributed to non-point sources, such as wastewater drainage and agricultural runoff.…”
Section: Single Indicessupporting
confidence: 93%
“…Environmental relevant trace elements concentrations, i.e. Cr, Cd, Pb and Hg, are similar to the ones observed in other mangrove soils (Alsamadany et al 2020;Angeli et al 2019;Chiu and Chou 1991;Kalaivanan et al 2017;Lacerda et al 1993;Machado et al 2014,Otero et al 2017b). These comparisons highlight the highly heterogeneity of the mangrove soils.…”
Section: Discussionsupporting
confidence: 81%
“…The observed TOC values in this study are relatively similar to mangrove soils from other semi-arid areas (Alsamadany et al 2020;Araújo et al 2012) but less than the average observed in mangroves soils from more humid areas located near the study region (Barreto 2008,Otero et al 2017b, which can be up to 20 %, and less than mangroves soils from other studies in humid regions (Chiu and Chou 1991;Marchand et al 2011).…”
Section: Discussionsupporting
confidence: 62%